Analisis Uji Beda Metode Pembelajaran Berbasis Masalah Menggunakan Media "Pohon Kebhinekaan" Terhadap Prestasi Belajar Siswa SMAN 1 Kademangan - Pratama, Denni; Triantoro, Miranu; Baihaqi, M. Iqbal (CIVITAS (JURNAL PEMBELAJARAN DAN ILMU CIVIC), 2025)
This study aims to analyse the differences in learning achievement between students taught using the problem-based learning (PBL) method with the ‘Tree of Diversity’ media and students taught using conventional methods in Pancasila Education at SMAN 1 Kademangan. This study uses a quantitative approach with a pretest-posttest control group quasi-experimental design. The research subjects consisted of two 10th-grade classes: an experimental class that received the PBL method treatment using the ‘Tree of Diversity’ media and a control class that used the conventional method. Data were collected through tests (pretest and posttest) and questionnaires to assess student responses. For the analysis, the T-test technique was used. The results of the study showed that there was a significant difference in learning achievement between the two groups, where students taught using the PBL method with the ‘Tree of Diversity’ media had a higher increase in learning achievement.  This can be seen from the learning achievement difference test result of -28.970, which is significantly lower than the t-table value of 1.693. This means that the use of the PBL method with the ‘Tree of Diversity’ media is more effective in supporting students' learning achievements at the high school level. Additionally, students' responses to the use of the method and media were very positive. This can be seen from the students' answers, which reached 44.24 out of a maximum score of 50. Thus, the results of this study also show that the use of learning media based on diversity values in the PBL method can improve the effectiveness of learning and students' understanding of Pancasila values